A comprehensive approach to the diagnosis, treatment and rehabilitation of patients with post-traumatic stress disorder, depression and comorbid arterial hypertension - Napreyenko Олександр; Alftian Абдулазіз (Psychosomatic Medicine and General Practice, 2025)
The article is devoted to the analysis of current directions of diagnostics, therapeutic intervention and rehabilitation approaches in the management of patients with (PTSD), depression and concomitant arterial hypertension (AH). The relevance of the problem in the conditions of Ukraine is highlighted, clinical features, psychometric diagnostic methods, drug and psychotherapeutic approaches are characterized. Special attention is paid to the importance of a multidisciplinary and integrative approach. A review of current literature and own considerations regarding the prospects for improving the mental health care system in Ukraine are presented. Objective. To assess the clinical and psychodiagnostic features of men with PTSD, non-cyclical depression, and hypertension, as well as the effectiveness of a comprehensive diagnostic and treatment program. To summarize current data on a comprehensive approach to the diagnosis, therapy, and rehabilitation of patients with PTSD, depression, and hypertension.